PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - SHOLAHUDDIN AL-AYYUBI, MUHAMMAD (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract This study to examine and analyze the influence of organizational culture on employee performance, the influence of work motivation on employee performance, the influence of organizational culture on work motivation and organizational culture affect employee performance through work motivation as an intervening variable. This is a quantitif research, which using analytical statistic Structural Equation Model (SEM) technique with Partial Least Square (PLS) analytical method, by collecting data randomly from 45 employees per division in the company.The results of this research state that organizational culture does not have a positive and insignificant impact on employee performance, intead of work motivation. So, work motivation is Intervening Variables that influencing organization culture. Keywords: Organization Culture, Employee Performance, Work Motivation